2008
DOI: 10.1021/es7026086
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Coliphage MS2 with Palladium-Modified Nitrogen-Doped Titanium Oxide Photocatalyst Illuminated by Visible Light

Abstract: A palladium-modified nitrogen-doped titanium oxide (TiON/-PdO) photocatalytic fiber was synthesized on a mesoporous activated carbon fiber template by a sol-gel process. Calcination of the coated fibers resulted in a macroporous interfiber structure and mesoporous photocatalyst coating. Atomic ratios of major photocatalyst constituents determined by X-ray photoelectron spectroscopy analyses were N/Ti approximately equal to 0.1 and Pd/-Ti approximately equal to 0.03. X-ray diffraction analyses revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 58 publications
1
60
0
1
Order By: Relevance
“…E. coli cells in log phase of growth in tryptic soy broth solution were collected as the host cells. MS2 were grown in E. coli suspensions and purified by sequential centrifugation and filtration with minor modifications (Li et al, 2008b). Briefly, after cell lysis and virus release, debris was removed via microfiltration through 0. w a t e r r e s e a r c h 6 9 ( 2 0 1 5 ) 5 9 e6 7…”
Section: Bacteriophagementioning
confidence: 99%
“…E. coli cells in log phase of growth in tryptic soy broth solution were collected as the host cells. MS2 were grown in E. coli suspensions and purified by sequential centrifugation and filtration with minor modifications (Li et al, 2008b). Briefly, after cell lysis and virus release, debris was removed via microfiltration through 0. w a t e r r e s e a r c h 6 9 ( 2 0 1 5 ) 5 9 e6 7…”
Section: Bacteriophagementioning
confidence: 99%
“…This is the case for a commercial non-concentrating solar CPC Some authors have investigated the cost of solar water disinfection (SODIS), using small scale CPC reactors for household users in developing countries. Ubomba-Jaswa and coworkers 48 reported that a 25L-CPC batch reactor could provide 70 solar disinfected water at a total treatment cost of $0.2 per 100L, taking into account that the estimated photo-reactor built cost is $200 with 10 years of operational life. An advantage of the CPC system is the modular system, and Polo-López and co-workers 49 reported that a 6-tube automated sequential CPC batch reactor 75 could provide solar disinfected water with a total cost of $0.23 per 100L.…”
Section: (Global) (Figure 8)mentioning
confidence: 99%
“…The concentric tube arrangement (a tube within a tube) with CPC was the most effective configuration. Photocatalysis has advantages in terms of the non-recovery of inactivated organisms and the inactivation of 70 SODIS resistant organisms. 57 Sordo and co-workers 60 studied the photocatalytic inactivation of E. coli with immobilized TiO 2 in two different configurations (a wall and a fixed-bed reactor) in a solar 10L-CPC pilot plant, comparing the use of a slurry reactor and the solar disinfection without catalyst.…”
Section: (Global) (Figure 8)mentioning
confidence: 99%
See 2 more Smart Citations